Room Temperature Metal Hydrides for Stationary and Heat Storage Applications: A Review - Modi, Poojan; Aguey-Zinsou, Kondo-Francois (Frontiers in Energy Research, 2021)
Hydrogen has been long known to provide a solution toward clean energy systems. With this notion, many efforts have been made to find new ways of storing hydrogen. As a result, decades of studies has led to a wide range of hydrides that can store hydrogen in a solid form. Applications of these solid-state hydrides are well-suited to stationary applications. However, the main challenge arises in making the selection of the Metal Hydrides (MH) that are best suited to meet application requirements. Herein, we discuss the current state-of-art in controlling the properties of room temperature (RT) hydrides suitable for stationary application and their long term behavior in addition to initial activation, their limitations and emerging trends to design better storage materials. The hydrogen storage properties and synthesis methods to alter the properties of these MH are discussed including the emerging approach of high-entropy alloys. In addition, the integration of intermetallic hydrides in vessels, their operation with fuel cells and their use as thermal storage is reviewed.